Long-Term Application of Bioorganic Fertilizers Improved Soil Biochemical Properties and Microbial Communities of an Apple Orchard Soil - Wang, Lei; Yang, Fang; E, Yaoyao; Yuan, Jun; Raza, Waseem; Huang, Qiwei; Shen, Qirong (Frontiers in Microbiology, 2016)
Soil biochemical properties and microbial communities are usually considered as important indicators of soil health because of their association with plant nutrition. In this study, we investigated the impact of long-term application of bioorganic fertilizer (BOF) on soil biochemical properties and microbial communities in the apple orchard soil of the Loess Plateau. The experiment included three treatments: (1) control without fertilization (CK); (2) chemical fertilizer application (CF); and (3) bioorganic fertilizer application (BOF). The high throughput sequencing was used to examine the bacterial and fungal communities in apple orchard soil. The results showed that the BOF treatment significantly increased the apple yield during the experimental time (2009-2015). The application of BOF significantly increased the activities of catalase and invertase compared to those in CK and CF treatments. The high throughput sequencing data showed that the application of BOF changed the microbial community composition of all soil depths considered (0-20cm, 20-40cm, and 40-60cm), e.g., the relative abundance of bio-control bacteria (Xanthomonadales, Lysobacter, Pseudomonas and Bacillus), Proteobacteria, Bacteroidetes, Ohtaekwangia, Ilyonectria and Lecanicillium was increased while that of Acidobacteria, Chloroflexi, Gp4, Gp6 and Sphaerobacter was decreased. The increase in apple yield after the application of BOF might be due to increase in organic matter, total nitrogen and catalase and invertase activities of soil and change in the bacterial community composition by enriching Bacillus, Pseudomonas, Lysobacter and Ohtaekwangia. These results further enhance the understanding on how BOFs alter soil microbial community composition to stimulate soil productivity.